Utilization of rice-mongo powder in cream of mushroom instant soup mix - Gomez, Ma. Theresa L.
Rice-mongo powder is a dry, powdered product from rice and a mung bean which was evaluated for its utilization as a soup filler in an instant Cream of Mushroom Soup Mix. The optimum level of rice-mongo powder substitution resulting to a product with increased nutritional value at the lowest possible cost was determined in the study. In Phase I, it was found that rice-mongo powder has a moisture and starch content of 5.8% and 5.04%, respectively, and the temperature required for gelatinization of the powder is 91°C. Rice-mongo powder was incorporated in the cream of mushroom soup formulation at 30%, 50% and 75% substitution levels for wheat flour in Phase II. Objective and sensory evaluation resulted to the selection of the 50% rice-mongo powder substituted soup, equivalent to 14.1% rice-mongo powder utilization, as the best among the soup samples tested. Thus in Phase III, proximate analysis and comparative analysis of nutritional values and costs of the selected soup was done. Protein, fat and fiber values were found to be higher for the rice-mongo powder substituted soup with % increase of 13.57%, 57.65% and 594.40%, respectively. The production costs incurred for the developed soup and the standard did not vary at P2.41 per unit package.